Improving EFL learners’ english public speaking performance through project-based learning strategy at tertiary level - Chuanfang, Shi; Asiah, Kassim; Noor Raha, Mohd Radzuan (European Knowledge Development Institute, 2024)
Traditional English education in China, with its emphasis on grammatical proficiency and written accuracy, often neglects public speaking, resulting in a notable deficiency in practical language application. This study investigated the potential of project-based learning to address this problem by promoting more interactive, student-centered learning experiences that foster authentic language use, specifically aiming to improve public speaking performance among university students in China, who are learning English as a foreign language (EFL). An explanatory sequential mixed method study, involving the pretest and post-test for quantitative data and semi-structured interviews for qualitative data, was conducted with 60 students purposely selected as the research participants. By the triangulation of the quantitative and qualitative findings, it was found that students in the experimental group who underwent the project-based learning intervention showed a significant improvement in English public speaking performance compared with the control group. In addition, students who participated in the interview held a positive attitude toward integrating project-based learning strategy into the process of learning English public speaking. These results contribute to the growing body of evidence supporting the adoption of project-based learning approach in EFL teaching, particularly in contexts where enhancing oral communication skills is a priority.